Segmentation Strategy of Streaming Media Based on Popularity Classifying - Yushan Deng; Ge Chen; Jun Zhang; Jie Liang (Dianxin kexue)
The characteristics of external and internal popularity of streaming media and the relationship of external popularity and the number of cache replacement were analyzed. Respecting the characteristics that cache replacements are focus on a small rang of popularity, a segmentation method based on popularity classifying of streaming media, which uses smaller segments on videos replaced frequently and bigger segments on the other videos, was proposed. The experimental result shows that the segmentation method can effectively reduce the number of segments compared with the uniform segmentation method under the same conditions of the byte hit ratio.